Legal Principles Of Regulation Of Foreign Economic Relations Of The Federative Republic Of Germany - Flissak, Kostiantyn (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The dynamics of global economic processes, increased competition in the international economic environment, the periodic occurrence of conflicts of interest between integration and disintegration processes, and challenges for national economies are a significant confirmation of the actuality of the subject of legal regulation, regulation and provision of foreign economic activity. Among main elements of Germany’s foreign economic activity that are subject to legal regulation, we should highlight, first of all, such as direct export-import operations, special export, attracting of foreign investments, customs tariff and non-tariff regulation, and state support for exports. In practice, foreign economic relations of Germany, movement of goods, services and capital with foreign countries, foreign trade turnover, as well as the movement of foreign valuables and gold between citizens are fundamentally free. However, there are certain restrictions in this area that arise from EU law and the Law on foreign economic activity of 6.06.2013, as well as from the Regulation on foreign economic activity. In the context of improving the verification of foreign investment, Germany has been working with France and Italy since 2017 to change the European Union legal framework for the verification of direct investments that are made by foreigners from the European Union. The focus is on improving the cooperation of EU member States in the field of investment audit, while opening up additional opportunities for action by national legislators. In the context of implementing Ukraine’s European integration intentions and actions, fully entering the free trade zone and ensuring compliance with and defending national interests, it is appropriate and relevant to take maximum account of Germany’s positive experience in regulating foreign economic relations with both EU countries and third countries. Given the complete absence of divisions and specialists in foreign diplomatic missions, as well as in the Ministry of foreign Affairs of Ukraine, whose main task should be a deep analysis of all components of the legal support of foreign economic processes of the host countries and partners of Ukraine, it is advisable to draw the attention of the Ministry of foreign Affairs and the Ministry of Economic Development, Trade and Agriculture of Ukraine to the need to solve this extremely important problem. Full possession of information on the legal support and regulation of foreign economic relations of the respective countries will enable Ukraine to guarantee the priority of national interests in cooperation with them and avoid actions that could negatively affect economic, food and energy security.